The fallen angel eaudiobook - Silva, Daniel (Gabriel Allon, 2015)
Number-one New York Times best-selling author Daniel Silva's thrilling Gabriel Allon novels have won comparisons to the works of John le CarrE. Here, ex-Israeli intelligence agent Allon is in Rome when he's asked by his friend Monsignor Luigi Donati, the private secretary to Pope Paul VII, to investigate a death at the Vatican. The victim- a beautiful woman- is thought to have committed suicide, but Allon soon learns that she had been harboring a deadly secret.